A high-temperature-resistant silicone defoaming agent for a butyronitrile latex system and a preparation method thereof
Patent Information
- Application Number
- CN202510493815.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-19
- Publication Date
- 2026-10-23
AI Technical Summary
这些泡沫会导致胶乳槽体积虚增、涂覆不均匀、制品孔隙率升高等问题,严重影响产品机械强度和密封性能
[0026]本发明制备的丁腈胶乳体系用耐高温有机硅消泡剂,通过采用由氧化锌包覆二氧化硅核壳结构、γ-氨丙基三乙氧基硅烷、多苯环硅氧烷偶联剂与正硅酸乙酯协同改性的分散填料使该消泡剂具有耐高温性强、破泡速度快、抑泡持久稳定等核心优势,解决了丁腈制品生产中的泡沫失控难题。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of defoamer technology, specifically relating to a high-temperature resistant organosilicon defoamer for nitrile latex systems and its preparation method. Background Technology
[0002] In the production process of nitrile rubber latex products (such as medical gloves and industrial seals), processes such as high-speed stirring, high-temperature vulcanization, and emulsion polymerization generate a large amount of stubborn foam. This foam can lead to problems such as artificially increased latex tank volume, uneven coating, and increased product porosity, seriously affecting the mechanical strength and sealing performance of the product. While polyether-modified silicone oil has instantaneous defoaming capabilities, traditional defoaming solutions have significant drawbacks in nitrile rubber latex systems: 1. Siloxane chains are easily broken during high-temperature vulcanization; 2. The defoamer has poor compatibility with the acrylonitrile polar groups in the latex, and adding more than 0.5% can cause an abnormal increase in latex viscosity; 3. Traditional hydrophobic silica fillers are prone to detaching from the silicone oil carrier during high-shear emulsification, resulting in insufficient defoaming durability.
[0003] Existing technologies such as CN108671590A, while improving stability through basalt fiber modification, still suffer from the defect of easy delamination at high temperatures. Furthermore, while carbon nanotube-silica composite filler (CN202410987584) used in high-temperature printing and dyeing is heat-resistant, its dispersibility has not been optimized for nitrile latex systems. Therefore, developing an environmentally friendly, efficient, and heat-resistant defoamer specifically for nitrile latex systems is particularly urgent. Summary of the Invention
[0004] In view of the shortcomings of the existing technology, the present invention develops a high-temperature resistant organosilicon defoamer for nitrile latex system. By using specific modified dispersing fillers, the high-temperature resistance and dispersion performance of the defoamer are further improved, and it has the advantages of short defoaming time, good foam suppression effect and good stability.
[0005] This invention is achieved through the following technical solution:
[0006] A high-temperature resistant silicone defoamer for nitrile latex systems is made from the following raw materials: silicone oil, modified composite filler, polysorbate 80, sorbitan oleate 80, thickener, preservative and water.
[0007] Preferably, a high-temperature resistant silicone defoamer for nitrile latex systems is prepared from the following raw materials in parts by weight: 30-70 parts by weight of silicone oil, 5-10 parts by weight of modified composite filler, 5-12 parts by weight of polysorbate 80, 8-20 parts by weight of sorbitan oleate 80, 2-6 parts by weight of thickener, 2-6 parts by weight of preservative and 150-380 parts by weight of water.
[0008] Preferably, the modified composite filler is prepared by the following method:
[0009] (a) Under nitrogen protection, 1-4 parts by weight of vinyltrimethoxysilane, 6-10 parts by weight of diphenyldimethoxysilane and 0.05-0.1 parts by weight of caster catalyst are mixed and stirred at 100-120°C for 10-15 hours, and the modified coupling agent is obtained by vacuum distillation.
[0010] (b) Disperse 20-30 parts by weight of nano-silica in 500-800 parts by weight of deionized water, adjust the pH to 9-10, add 5-8 parts by weight of zinc nitrate and 2-4 parts by weight of urea, stir at 80-90°C for 3-5 hours to form a ZnO coating layer;
[0011] (c) After centrifuging and washing the product of step (b), disperse it together with 0.5 to 2 parts by weight of γ-aminopropyltriethoxysilane and 0.5 to 1.5 parts by weight of the modified coupling agent obtained in step (a) in 800 to 1200 parts by weight of ethanol aqueous solution, and sonicate for 1 to 2 hours.
[0012] (d) Add 0.3 to 0.8 parts by weight of tetraethyl orthosilicate, stir at 70 to 90°C for 6 to 8 hours, and centrifuge and dry to obtain a modified composite filler with a core-shell structure.
[0013] This invention uses nano-silica as the core material and forms a core-shell structure by coating the surface with a zinc oxide shell through a sol-gel method. Utilizing the high thermal conductivity and wide bandgap semiconductor properties of zinc oxide, the thermal stability of the defoamer in nitrile latex at high temperatures is significantly improved. Subsequently, through synergistic modification with a polycyclic siloxane coupling agent and γ-aminopropyltriethoxysilane, a modified core-shell filler is finally obtained. This filler achieves rapid dispersion in nitrile latex within a short time and, through the polar gradient of the zinc oxide shell, directionally adsorbs foaming substances, thereby increasing the drainage rate of the foam liquid film and effectively avoiding porosity and surface defects in the product.
[0014] First, this invention constructs a core-shell structure of zinc oxide coated with silica, using nano-silica as the core and forming a core-shell composite system by coating the surface with a zinc oxide shell. By utilizing the high thermal conductivity and wide bandgap semiconductor properties of zinc oxide, the performance of defoamers is synergistically improved. The zinc oxide shell effectively blocks heat transfer in nitrile latex at high temperatures, preventing the decomposition of silicone oil carrier. At the same time, the silica core adsorbs surfactants, and the zinc oxide shell decomposes foaming substances through photocatalysis, thus accelerating foam breakage through a dual-effect synergy.
[0015] Secondly, this invention optimizes the performance of the filler through molecular structure modification. It uses vinyltrimethoxysilane and diphenyldimethoxysilane to condense and generate a polyphenyl ring siloxane coupling agent. Its large-volume benzene ring side groups form a thermal barrier, enhancing the high-temperature resistance of the filler. It introduces γ-aminopropyltriethoxysilane, which improves the dispersion stability and prevents the filler from agglomerating through the hydrogen bonding between the amino group and the latex component. The tetraethyl orthosilicate hydrolyzes to generate a three-dimensional cross-linked network, which enhances the shear resistance of the core-shell filler and enables it to maintain its structural integrity during high-shear stirring of latex.
[0016] Preferably, the concentration of the ethanol aqueous solution is 60-80 wt%.
[0017] Preferably, the silicone oil is one or a mixture of two or more of the following: hydrogen-containing silicone oil, dimethyl silicone oil, phenylmethyl silicone oil, and vinyl silicone oil.
[0018] Preferably, the thickener is one or a mixture of two or more of polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose, and sodium carboxymethyl cellulose.
[0019] Preferably, the preservative is any one of sodium formate, potassium sorbate, sodium nitrite, and sodium benzoate.
[0020] This invention also provides a method for preparing a high-temperature resistant silicone defoamer for the above-mentioned nitrile latex system, comprising the following steps:
[0021] S1: Weigh 30-70 parts by weight of silicone oil, 5-10 parts by weight of modified composite filler, 5-12 parts by weight of polysorbate 80, 8-20 parts by weight of sorbitan oleate 80, 2-6 parts by weight of thickener, 2-6 parts by weight of preservative and 150-380 parts by weight of water, and set aside.
[0022] S2: Mix the organosilicon oil with the modified composite filler, stir and react in an oil bath at 300-450°C for 2-4 hours, and cool to 60-80°C for later use;
[0023] S3: Mix polysorbate 80, sorbitan oleate 80 with water, stir in a water bath at 60-90°C for 20-40 minutes, slowly add the mixture from step S2, and continue stirring for 10-25 minutes;
[0024] S4: Add thickener and preservative, stir until uniform, and cool to obtain the defoamer.
[0025] The advantages of this invention are:
[0026] The high-temperature resistant silicone defoamer for nitrile latex systems prepared in this invention has core advantages such as strong high-temperature resistance, fast foam breaking speed, and long-lasting and stable foam suppression by using a dispersion filler synergistically modified with zinc oxide-coated silica core-shell structure, γ-aminopropyltriethoxysilane, polyphenylcyclosiloxane coupling agent and tetraethyl orthosilicate, thus solving the problem of foam runaway in the production of nitrile products. Detailed Implementation
[0027] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Example 1
[0029] A high-temperature resistant silicone defoamer for nitrile latex systems includes the following steps:
[0030] S1: Weigh 30 parts by weight of dimethyl silicone oil, 5 parts by weight of modified composite filler, 5 parts by weight of polysorbate 80, 8 parts by weight of sorbitan oleate 80, 2 parts by weight of thickener hydroxyethyl cellulose, 2 parts by weight of preservative sodium benzoate and 150 parts by weight of water, and set aside; wherein, the viscosity of dimethyl silicone oil is 500 mPa.s.
[0031] S2: Mix dimethyl silicone oil with modified composite filler, stir and react in an oil bath at 300°C for 2 hours, and cool to 60°C for later use.
[0032] S3: Mix polysorbate 80, sorbitan oleate 80 and water, stir in a 60°C water bath for 20 minutes, slowly add the mixture from step S2, and continue stirring for 10 minutes;
[0033] S4: Add the thickener hydroxyethyl cellulose and the preservative sodium benzoate, stir until uniform, and cool to obtain the defoamer.
[0034] The modified dispersion filler was prepared by the following method:
[0035] (a) Under nitrogen protection, 1 part by weight of vinyltrimethoxysilane, 6 parts by weight of diphenyldimethoxysilane and 0.05 to 0.1 parts by weight of caster catalyst were mixed and stirred at 100°C for 10 hours. The modified coupling agent was obtained by vacuum distillation.
[0036] (b) Disperse 20 parts by weight of nano-silica in 500 parts by weight of deionized water, adjust the pH to 8, add 5 parts by weight of zinc nitrate and 2 parts by weight of urea, stir at 80°C for 3 hours to form a ZnO coating layer.
[0037] (c) After centrifuging and washing the product of step (b), it is dispersed together with 0.5 parts by weight of γ-aminopropyltriethoxysilane and 0.5 parts by weight of the modified coupling agent obtained in step (a) in 800 parts by weight of 60wt% ethanol aqueous solution and ultrasonically treated for 1 hour.
[0038] (d) Add 0.3 parts by weight of tetraethyl orthosilicate, stir at 70°C for 6 hours, and centrifuge and dry to obtain a modified composite filler with a core-shell structure.
[0039] Example 2
[0040] A high-temperature resistant silicone defoamer for nitrile latex systems includes the following steps:
[0041] S1: Weigh 30 parts by weight of dimethyl silicone oil, 5 parts by weight of modified composite filler, 5 parts by weight of polysorbate 80, 8 parts by weight of sorbitan oleate 80, 2 parts by weight of thickener hydroxyethyl cellulose, 2 parts by weight of preservative sodium benzoate and 150 parts by weight of water, and set aside; wherein, the viscosity of dimethyl silicone oil is 500 mPa.s.
[0042] S2: Mix dimethyl silicone oil with modified composite filler, stir and react in an oil bath at 300°C for 2 hours, and cool to 60°C for later use.
[0043] S3: Mix polysorbate 80, sorbitan oleate 80 and water, stir in a 60°C water bath for 20 minutes, slowly add the mixture from step S2, and continue stirring for 10 minutes;
[0044] S4: Add the thickener hydroxyethyl cellulose and the preservative sodium benzoate, stir until uniform, and cool to obtain the defoamer.
[0045] The modified dispersion filler was prepared by the following method:
[0046] (a) Disperse 20 parts by weight of nano-silica in 500 parts by weight of deionized water, adjust the pH to 8, add 5 parts by weight of zinc nitrate and 2 parts by weight of urea, stir at 80°C for 3 hours to form a ZnO coating layer.
[0047] (b) After centrifuging and washing the product of step (a), it is dispersed together with 0.5 parts by weight of γ-aminopropyltriethoxysilane and 0.5 parts by weight of the modified coupling agent obtained in step (a) in 800 parts by weight of 60 wt% ethanol aqueous solution and ultrasonically treated for 1 hour.
[0048] (c) Add 0.3 parts by weight of tetraethyl orthosilicate, stir at 70°C for 6 hours, and centrifuge and dry to obtain a modified composite filler with a core-shell structure.
[0049] Example 3
[0050] A high-temperature resistant silicone defoamer for nitrile latex systems includes the following steps:
[0051] S1: Weigh 30 parts by weight of dimethyl silicone oil, 5 parts by weight of modified composite filler, 5 parts by weight of polysorbate 80, 8 parts by weight of sorbitan oleate 80, 2 parts by weight of thickener hydroxyethyl cellulose, 2 parts by weight of preservative sodium benzoate and 150 parts by weight of water, and set aside; wherein, the viscosity of dimethyl silicone oil is 500 mPa.s.
[0052] S2: Mix dimethyl silicone oil with modified composite filler, stir and react in an oil bath at 300°C for 2 hours, and cool to 60°C for later use.
[0053] S3: Mix polysorbate 80, sorbitan oleate 80 and water, stir in a 60°C water bath for 20 minutes, slowly add the mixture from step S2, and continue stirring for 10 minutes;
[0054] S4: Add the thickener hydroxyethyl cellulose and the preservative sodium benzoate, stir until uniform, and cool to obtain the defoamer.
[0055] The modified dispersion filler was prepared by the following method:
[0056] (a) Mix 1 part by weight of vinyltrimethoxysilane and 6 parts by weight of diphenyldimethoxysilane to obtain a coupling agent mixture.
[0057] (b) Disperse 20 parts by weight of nano-silica in 500 parts by weight of deionized water, adjust the pH to 8, add 5 parts by weight of zinc nitrate and 2 parts by weight of urea, stir at 80°C for 3 hours to form a ZnO coating layer.
[0058] (c) After centrifuging and washing the product of step (b), it is dispersed together with 0.5 parts by weight of γ-aminopropyltriethoxysilane and 0.5 parts by weight of the modified coupling agent obtained in step (a) in 800 parts by weight of 60 wt% ethanol aqueous solution and ultrasonically treated for 1 hour.
[0059] (d) Add 0.3 parts by weight of tetraethyl orthosilicate, stir at 70°C for 6 hours, and centrifuge and dry to obtain a modified composite filler with a core-shell structure.
[0060] Example 4
[0061] A high-temperature resistant silicone defoamer for nitrile latex systems includes the following steps:
[0062] S1: Weigh 30 parts by weight of dimethyl silicone oil, 5 parts by weight of modified composite filler, 5 parts by weight of polysorbate 80, 8 parts by weight of sorbitan oleate 80, 2 parts by weight of thickener hydroxyethyl cellulose, 2 parts by weight of preservative sodium benzoate and 150 parts by weight of water, and set aside; wherein, the viscosity of dimethyl silicone oil is 500 mPa.s.
[0063] S2: Mix dimethyl silicone oil with modified composite filler, stir and react in an oil bath at 300°C for 2 hours, and cool to 60°C for later use.
[0064] S3: Mix polysorbate 80, sorbitan oleate 80 and water, stir in a 60°C water bath for 20 minutes, slowly add the mixture from step S2, and continue stirring for 10 minutes;
[0065] S4: Add the thickener hydroxyethyl cellulose and the preservative sodium benzoate, stir until uniform, and cool to obtain the defoamer.
[0066] The modified dispersion filler was prepared by the following method:
[0067] (a) Under nitrogen protection, 1 part by weight of vinyltrimethoxysilane, 6 parts by weight of diphenyldimethoxysilane and 0.05-0.1 parts by weight of caster catalyst were mixed and stirred at 100°C for 10 hours. The modified coupling agent was obtained by vacuum distillation.
[0068] (b) Add 12.5 parts by weight of silica and 17.5 parts by weight of nano-silica to 800 parts by weight of 60 wt% ethanol aqueous solution and sonicate for 0.5 hours;
[0069] (c) Add 0.5 parts by weight of γ-aminopropyltriethoxysilane, 0.5 parts by weight of the modified coupling agent obtained in step (a) and 0.2 parts by weight of tetraethyl orthosilicate to the mixture in step (b), stir at 70°C for 8 hours, and centrifuge and dry to obtain the modified composite filler.
[0070] Example 5
[0071] A high-temperature resistant silicone defoamer for nitrile latex systems includes the following steps:
[0072] S1: Weigh 30 parts by weight of dimethyl silicone oil, 5 parts by weight of silica, 5 parts by weight of polysorbate 80, 8 parts by weight of sorbitan oleate 80, 2 parts by weight of thickener hydroxyethyl cellulose, 2 parts by weight of preservative sodium benzoate and 150 parts by weight of water, and set aside; wherein, the viscosity of dimethyl silicone oil is 500 mPa.s;
[0073] S2: Mix dimethyl silicone oil with silicon dioxide, stir and react in an oil bath at 300°C for 2 hours, and then cool to 60°C for later use.
[0074] S3: Mix polysorbate 80, sorbitan oleate 80 and water, stir in a 60°C water bath for 20 minutes, slowly add the mixture from step S2, and continue stirring for 10 minutes;
[0075] S4: Add the thickener hydroxyethyl cellulose and the preservative sodium benzoate, stir until uniform, and cool to obtain the defoamer.
[0076] We designed a set of comparative experiments, selecting a sample of an organosilicon defoamer, denoted as Sample A. Under the same conditions, its high-temperature resistance, defoaming time, foam suppression time, and centrifugal stability were tested and compared with five embodiments of the present invention.
[0077] Test Example 1
[0078] Temperature resistance test: Add 200 ml of water to a 500 ml beaker, then add 4 ml of defoamer solution (the defoamer and water solution are diluted at a ratio of 1:20) and start heating. Record the temperature when flocculent matter appears on the liquid surface; this is the precipitation temperature of the defoamer. Continue heating to boiling for 5 minutes, then cool to room temperature and observe the state of the liquid surface. The more plus signs (+) there are, the more severe the precipitation.
[0079] Table 1. Temperature resistance of defoamers
[0080] Precipitation temperature (°C) Precipitation status Example 1 87.2 + Example 2 82.6 ++ Example 5 60.4 ++++ Sample A 74.3 +++
[0081] Test Example 2
[0082] Defoaming test: Take 30 ml of foaming solution (1.0 wt% sodium dodecylbenzenesulfonate aqueous solution) in a 100 ml graduated cylinder, add it to the bubbling head, and use a bubbling machine to generate foam. Stop bubbling when the foam rises to the level of the graduated cylinder opening. Under constant temperature of 60℃, spray 10 ml of defoamer diluted solution (1 ml of defoamer stock solution diluted in 100 ml of water) with a syringe. Immediately after spraying, start timing and record the time taken for the foam to disappear until the liquid surface appears. Record this as the defoaming time (s). Perform 5 parallel tests and take the average value.
[0083] Defoaming test: In the defoaming test, after the foam has subsided to the liquid level, the bubbler is restarted and the timer is started immediately. The time it takes for the foam height to reach the measuring cylinder opening again is recorded as the defoaming time (s). Five parallel groups are tested, and the average value is taken.
[0084] Centrifugal stability test: Add 0.5 g of defoamer to 100 ml of water, stir well, centrifuge at 3000 r / min for 5 minutes, and observe the centrifugal stability of the sample. If there is no stratification, it proves that the centrifugal stability is good.
[0085] Table 2. Defoaming time, foam suppression time and centrifugal stability of defoamers
[0086] Defoaming time (s) Defoaming time (s) stability Example 1 20.3 35.8 Unlayered Example 2 28.8 28.2 Unlayered Example 3 25.4 32.6 Unlayered Example 4 23.5 30.4 Unlayered Example 5 74 20.5 Slight stratification Sample A 60.2 23.4 Unlayered
[0087] According to the test results, the high-temperature resistant silicone defoamer for nitrile latex systems prepared in Example 1 of this invention exhibits significant comprehensive advantages. Its precipitation temperature reaches 87.2℃, and after high-temperature boiling, it only slightly precipitates (+), far superior to Examples 2-5 and comparative sample A, indicating its outstanding high-temperature resistance. In the defoaming performance test, Example 1's defoaming time is only 20.3 seconds, and its foam suppression time reaches 35.8 seconds, with excellent centrifugal stability, showing significantly better overall performance than other examples and traditional sample A. This advantage stems from the unique modified composite filler design in Example 1: using nano-silica as the core, a zinc oxide shell is coated via a sol-gel method to construct a core-shell structure. The high thermal conductivity of zinc oxide blocks heat transfer during high-temperature processes, protecting the silicone oil carrier from decomposition; its wide bandgap semiconductor properties accelerate foam rupture through photocatalysis, increasing the foam liquid film drainage rate. Meanwhile, a polycyclic siloxane coupling agent is formed by the condensation of vinyltrimethoxysilane and diphenyldimethoxysilane. The large-volume benzene ring side groups of this coupling agent form a thermal barrier, which, combined with the amino hydrogen bonding of γ-aminopropyltriethoxysilane, significantly enhances the dispersion stability of the filler in nitrile latex. Furthermore, the three-dimensional cross-linked network formed by the hydrolysis of tetraethyl orthosilicate further improves the filler's shear resistance, ensuring its defoaming activity is maintained at high temperatures.
[0088] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A high-temperature resistant silicone defoamer for nitrile latex systems, characterized in that, Made from the following raw materials: Organosilicon oil, modified composite filler, polysorbate 80, sorbitan oleate 80, thickener, preservative and water; wherein, the modified composite filler is prepared by the following method: using silica as the core, coating the surface with a zinc oxide shell by sol-gel method, then reacting it with a modified coupling agent in an ethanol aqueous solution by ultrasonic dispersion, and centrifugation and drying. The modified coupling agent is a polycyclic siloxane formed by the condensation of vinyltrimethoxysilane and diphenyldimethoxysilane under the action of a cascade catalyst.
2. The high-temperature resistant silicone defoamer for nitrile latex systems as described in claim 1, characterized in that, The preparation method of the modified composite filler includes the following steps: (a) Under nitrogen protection, 1-4 parts by weight of vinyltrimethoxysilane, 6-10 parts by weight of diphenyldimethoxysilane and 0.05-0.1 parts by weight of caster catalyst are mixed and stirred at 100-120°C for 10-15 hours, and the modified coupling agent is obtained by vacuum distillation. (b) Disperse 20-30 parts by weight of nano-silica in 500-800 parts by weight of deionized water, adjust the pH to 9-10, add 5-8 parts by weight of zinc nitrate and 2-4 parts by weight of urea, stir at 80-90°C for 3-5 hours to form a ZnO coating layer; (c) After centrifuging and washing the product of step (b), disperse it together with 0.5 to 2 parts by weight of γ-aminopropyltriethoxysilane and 0.5 to 1.5 parts by weight of the modified coupling agent obtained in step (a) in 800 to 1200 parts by weight of ethanol aqueous solution, and sonicate for 1 to 2 hours. (d) Add 0.3 to 0.8 parts by weight of tetraethyl orthosilicate, stir at 70 to 90°C for 6 to 8 hours, and centrifuge and dry to obtain a modified composite filler with a core-shell structure.
3. The high-temperature resistant silicone defoamer for nitrile latex systems as described in claim 1, characterized in that, Made from the following ingredients by weight: 30-70 parts by weight of silicone oil, 5-10 parts by weight of modified composite filler, 5-12 parts by weight of polysorbate 80, 8-20 parts by weight of sorbitan oleate 80, 2-6 parts by weight of thickener, 2-6 parts by weight of preservative and 150-380 parts by weight of water.
4. The high-temperature resistant silicone defoamer for nitrile latex systems as described in claim 1, characterized in that, The silicone oil is one or a mixture of two or more of the following: hydrogen-containing silicone oil, dimethyl silicone oil, phenylmethyl silicone oil, and vinyl silicone oil.
5. The high-temperature resistant silicone defoamer for nitrile latex systems as described in claim 1, characterized in that, The thickener is one or a mixture of two or more of polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose, and sodium carboxymethyl cellulose.
6. The high-temperature resistant silicone defoamer for nitrile latex systems as described in claim 1, characterized in that, The preservative is any one of sodium formate, potassium sorbate, sodium nitrite, and sodium benzoate.
7. The method for preparing the high-temperature resistant organosilicon defoamer for nitrile latex systems according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Mix the organosilicon oil with the modified composite filler, stir and react in an oil bath at 300-450°C for 2-4 hours, and cool to 60-80°C for later use; S2: Mix polysorbate 80, sorbitan oleate 80 and water, stir in a water bath at 60-90°C for 20-40 minutes, slowly add the mixture from step S1, and continue stirring for 10-25 minutes; S3: Add thickener and preservative, stir until uniform, and cool to obtain the defoamer.
Citation Information
Patent Citations
Efficient deodorization type modified organic silicon defoamer for sewage treatment and preparation method thereof
CN108671590A
High-temperature printing and dyeing defoaming agent and preparation method thereof
CN118512803A
